Characteristics of the Islamic Education System in Thailand - Hadini Hadini; Hayati Hayati; Nurbayani Nurbayani (International Journal of Social Service and Research, 2023)
The uniqueness of the Islamic Education institution system in Thailand is certainly interesting to be studied in more depth, because it is a wealth of treasures owned by Islam that should be proud of in front of other worlds, the study of these institutions is also considered important to be taken for the development of the Islamic Education system wherever it is, as well as a filter wisdom to face the times in the industrial and information era 4.0 today. In exploring information related to the characteristics of Islamic Education institutions in Thailand, researchers tried to use the library research method. For this reason, researchers searched the literature in the form of books, research results, and journals, both national and international related to the topic being studied, namely examining the characteristics of the Islamic educational institution system that developed in Thailand. From the search results it was found that Islamic educational institutions in Thailand are in the form of houses, mosques / mosques, huts and madrasas. Islamic education began with studying Al-Our'an in Mushola (Balai Shah), Mosques and houses. Guru or "Tok Guru Al-Qur'an" is in charge of producing religious figures such as Imam, Khatib, Bilal, every Mosque, members of the mosque power department and at least become spiritual leaders (Tok Leba). The material is the classics. The students are called Tok Pake while the teachers are called Tok guru. While Madrasah has a more modern system with a classical system. Furthermore, the Thai government's policy towards Islamic education is accommodating.